Dog activity in protected areas: behavioral effects on mesocarnivores and the impacts of a top predator - de Cassia Bianchi, Rita [UNESP]; Olifiers, Natalie; Riski, Letícia Lutke; Gouvea, Jéssica Abonízio [UNESP]; Cesário, Clarice Silva [UNESP]; Fornitano, Larissa [UNESP]; Zanirato, Gisele Lamberti [UNESP]; Yan de Oliveira, Mateus [UNESP]; de Morais, Kimberly Danielle Rodrigues [UNESP]; Ribeiro, Renan Lieto Alves [UNESP]; D’Andrea, Paulo Sergio; Gompper, Matthew E. (Springer Nature, 2020)
Free-ranging dogs (Canis familiaris) negatively impact wildlife worldwide. Yet despite being members of the order Carnivora, we have relatively little information on the role that dogs play in carnivore communities. To evaluate if activity patterns of wild carnivores are influenced by the activity of dogs and if the latter is influenced by the activity of pumas (Puma concolor), we placed camera traps in eight protected areas in São Paulo State and in six in Rio de Janeiro State, Brazil, from 2011 to 2017. We obtained 551 photo-captures of dogs in 20,524 trap nights in 11 of the 14 protected areas. Dogs were active primarily during the day and therefore overlapped mainly with diurnal carnivores, such as tayras (Eira barbara) and coatis (Nasua nasua). Mesocarnivore temporal activity did not appear affected by the activity of dogs, since the activity patterns of tayras, coatis, maned wolves (Chrysocyon brachyurus), and ocelots (Leopardus pardalis) were similar (from 67 to 82% of overlap) in areas with and without dogs. Further, the activity of dogs was not influenced by puma activity; dog activity patterns in areas with pumas and without pumas overlapped by 84%, with minimal differences. While mesocarnivores might alter their spatial behavior to avoid overlap with dogs, it appears that dog use of protected areas does not result in shifts in the temporal activity of mesocarnivores. Further, we hypothesize that dogs that use protected areas are mostly provisioned by humans (owners), and therefore, their activity patterns may be more related to that of their owners than to the presence of native carnivore species.
Keywords: Activity patterns; Alien species; Canis familiaris; Eira barbara; Invasive predator; Nasua nasua; Puma concolor